Inhibition of cell proliferation by 2-fluorobenzaldehyde retinoic acid conjugate through suppression of STAT3 activation in human glioma cells - Ji-Heng Hao; Dian-Feng Hu; Li-Mei Mao; Shi-Gang Zhang; Ji-Yue Wang; Gang Li (Bangladesh Pharmacological Society, 2015)
The present study was performed to investigate the effect of 2-fluorobenzaldehyde retinoic acid conjugate on activation of STAT3 pathway in human glioma cells. The results revealed that the compound exhibited inhibitory effect on the activation of STAT3 induced constitutively and by interleukin-6. The inhibitory effect on STAT3 activation was found to be concentration- and time-dependent. In U373 glioma cells, 2-fluorobenzaldehyde retinoic acid conjugate treatment caused a significant enhancement in the expression of proapoptotic proteins like Bax and Bak. Its treatment inhibited the expression of genes including, cyclin D1, Bcl-2, Bcl-xL, survivin, Mcl-1, and vascular endothelial growth factor (VEGF) in U373 glioma cells. Furthermore, the conjugate inhibited proliferation, induced apoptosis and caused accumulation of cells in G1-G0 phase of cell cycle. Thus, 2-fluorobenzaldehyde retinoic acid conjugate acts as a potent inhibitor of STAT3 activation that can be promising importance for the prevention and treatment of gliomas.